Comparison of Postoperative Pain Scores in Laparoscopic Cholecystectomy with Infiltration of Intraperitoneal Bupivacaine and Bupivacaine Plus Hydrocortisone - Toor, Sana Zahid; Khalid, Fizzah; Khan, Waseem Ahmed; Niaz, Muhammad Muttahhar Asim; Khurshid, Hira; Gull , Mehreen (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare postoperative pain scores in patients who underwent laparoscopic cholecystectomy (LC) with infiltration of intraperitoneal Bupivacaine vs Bupivacaine plus Hydrocortisone. Study Design: Quasi-experimental study. Place And Duration Of Study: Department of General Surgery, Pak Emirates Military Hospital Rawalpindi, Pakistan from Nov 2024 to Jun 2025. Methodology: Ninety (n=90) patients underwent LC under general anesthesia. Participants were segregated into two groups. In Group-A, intraperitoneal instillation of Bupivacaine was done and in Group-B, intraperitoneal instillation of Bupivacaine plus Hydrocortisone was done. After the surgery, abdominal pain was compared between the two groups. Statistical Package for Social Sciences 23 was utilized to assess data. Results: Ninety (n=90) patients were included in the study and equally segregated into two groups. In Group-A, at 02 hours posts surgery significant pain was present in7(15.55%) patients and in Group-B, in 3(6.66%) patients(p-value:0.18). In Group-A, at 06 hours posts surgery significant pain was present in 5(11.11%) patients and in Group-B in 2(4.44%) patients, (p-value:0.23). In Group-A, at 12 hours posts surgery significant pain was present in2(4.44%) patients and in Group-B in 3(6.66%) patients, (p-value:0.64). In Group-A, at 24 hours posts surgery significant pain was present in 4 (8.88%) patients and in Group-B in 1(2.22%) patient, (p-value:0.16). Conclusion: No significant difference was found between instillation of intraperitoneal Bupivacaine vs Bupivacaine plus Hydrocortisone in terms of post- operative abdominal pain.